2021
DOI: 10.1186/s12967-021-03190-w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the trajectory of the urine output for 24 h on the occurrence of AKI in patients with sepsis in intensive care unit

Abstract: Background Sepsis-associated acute kidney injury (S-AKI) is a common and life-threatening complication in hospitalized and critically ill patients. This condition is an independent cause of death. This study was performed to investigate the correlation between the trajectory of urine output within 24 h and S-AKI. Methods Patients with sepsis were studied retrospectively based on the Medical Information Mart for Intensive Care IV. Latent growth mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…adopted RIFLE criteria. Recent research by Zhang and coworkers found that the incidence of AKI in sepsis was 41.1% in the mimic IV database ( 19 ), the results of this study support the findings of Luming Zhang and other colleges. The above studies indicate that patients with Sepsis AKI are still diseases that require urgent attention in critical care medicine.…”
Section: Discussionsupporting
confidence: 88%
“…adopted RIFLE criteria. Recent research by Zhang and coworkers found that the incidence of AKI in sepsis was 41.1% in the mimic IV database ( 19 ), the results of this study support the findings of Luming Zhang and other colleges. The above studies indicate that patients with Sepsis AKI are still diseases that require urgent attention in critical care medicine.…”
Section: Discussionsupporting
confidence: 88%
“…Treatment regimens for AKI have been unsuccessful over the years due to a lag in the clinical recognition of AKI with serum creatinine 17 . Some studies have also successively confirmed that oliguria is an early predictor of higher mortality in critically ill patients 18–20 . However, changes in urine output have shown high specificity only in oliguric AKI.…”
Section: Discussionmentioning
confidence: 99%
“…and the Beth Israel Deaconess Medical Center (Boston, Mass. ), and consent was obtained for collection of the original data ( Zhang et al, 2021 ). The database also anonymizes patient information, and so informed consent did not need to be obtained.…”
Section: Methodsmentioning
confidence: 99%